The Application of Eucalyptus Oil Aromatherapy in Reducing Nausea in Breast Cancer Patients During Chemotherapy: A Case Study at Gunung Jati Regional General Hospital, Cirebon City - Riah, Suci; Purbasari, Dwiyanti; Karlina, Nonok (INDOGENIUS, 2025)
Background & Objective: Nausea is a common side effect of chemotherapy in breast cancer patients, which can interfere with patient comfort and nutritional status. Aromatherapy is known to have the potential to reduce these complaints non-pharmacologically. Method: This study is a case study with a qualitative descriptive approach, conducted in the HOT ward of Gunung Jati General Hospital in Cirebon City. Data were collected through nursing care assessments and documentation of breast cancer patients undergoing chemotherapy who experienced nausea. The intervention involved the administration of eucalyptus oil aromatherapy, as well as education and emotional support. Result: After continuous aromatherapy administration, patients showed a decrease in nausea intensity from a scale of 4 to a milder level. Patients also felt more emotionally calm, hydration patterns improved, and overall comfort increased. Conclusion: Eucalyptus oil aromatherapy is effective as an additional intervention to reduce chemotherapy-induced nausea in breast cancer patients. This approach also supports a holistic nursing approach in improving patients' quality of life.